The Role of UN Women in the Implementation of SDG 5 in Conflict Area: A Case Study of Palestine - Gultom, Yosua Saut Marulitua (Jisiera: The Journal of Islamic Studies and International Relations, 2024)
This article discusses UN Women's role in implementing gender equality under Sustainable Development Goal (SDG) 5 in Palestine, a region prone to ongoing conflict with Israel. Women in conflict zones are often victims of physical, sexual and psychological violence and experience limited access to health and education services. UN Women, as a UN agency that focuses on gender equality, has an important role in encouraging the implementation of SDG 5 in conflict areas such as Palestine. Using descriptive qualitative research methods, this article analyzes the history and role of UN Women, the relationship between SDG 5 and conflict areas, and indications of gender inequality in the Palestinian conflict, such as violence against women and limited access to health services. Based on this analysis, the research question formulated is "How is UN Women's role in implementing gender equality contained in SDG 5 as a global agenda in situations in areas that are prone to prolonged conflict such as in Palestine?" This article aims to describe and analyze the role of UN Women in promoting gender equality in Palestine and to look at the effectiveness of SDGs in advancing gender equality in the midst of conflict.